Treatment of a Chronic Vulvar Wound by Hyperbaric Oxygen Therapy (HBOT) - D. Ricard-Gauthier; M.-A. Panchard; D. E. Huber (Case Reports in Obstetrics and Gynecology)
We hereby report the case of a 66-year-old obese patient (BMI 30) with type 2 diabetes, who presented a chronic vulvar lesion on the left labia majora following surgical drainage of an abscess. After multiple unsuccessful treatments by antibiotics and local wound care, we proposed a trial of hyperbaric oxygen therapy (HBOT). The patient fully recovered after 54 sessions at 2.5 ATA, 95 minutes each. HBOT has been studied for perineal lesion such as skin atrophy or necrosis caused by irradiation but not for vulvar nonhealing chronic lesions in the case of impaired vascularization caused by diabetes. This case is, to our knowledge, one of the first publications about the healing boost of HBOT in chronic vulvar wounds due to vascular impairment.